Strong Convergence of an Implicit -Iterative Process for Lipschitzian Hemicontractive Mappings - Shin Min Kang; Arif Rafiq; Sunhong Lee (Abstract and Applied Analysis)
We establish the strong convergence for the implicit -iterative process associated with Lipschitzian hemicontractive mappings in Hilbert spaces.